HUMAN DEVELOPMENT IN MINORITY COMMUNITIES: A STORY OF GROWTH - Sarita Riski Nasution; Liah Rosdiani Nasution (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
A huge number of immigrant families live and work in America where most aspects of lives are remotely similar to the ones we have here in Indonesia, for instance. Many of their children experience some unique developmental realities that are different from the ones experienced by children in some other parts of the world. Some experience challenges in their growth through the dynamics of their relationship with others, particularly their family members. Some others experience it because of their socioeconomic status. This study looks at children from Asian minority communities growing up in the US, Zahra and Linda. Understanding their developments is deemed critical to help us understand the distinction of their developments. Zahra is from Saudi Arabia and lives with her parents in Northern Albuquerque and Linda is from Indonesia, living in California. For Zahra, Arabic is her first language and she is still learning English at this time. Linda, however, was born in Indonesia but raised since she was 3 months old in the US which makes English her first language, although her family still uses Indonesian at home. By observing them, we can gain great insights into their cognitive, social, and physical development and utilize that knowledge to better understand childhood and adolescent development within the immigrant community as a whole